N,N,N′,N′-Tetramethylethylenediammonium tetrachloridozincate - Islam Ullah Khan; Maqsood Ahmed; Mohammed Fettouhi; Muhammad Akhtar; Saeed Ahmad (Acta Crystallographica Section E, 2013)
The asymmetric unit of the title compound, (C6H18N2)[ZnCl4], consists of one tetrachloridozincate anion and two half-N,N,N′N′-tetramethylethylenediammonium cations. Each of the two diammonium cations is located about an inversion center and one of them is disordered over two sets of sites in a 0.780 (17):0.220 (17) ratio. The ZnII atom has a slightly distorted tetrahedral coordination environment. The cations and anions are connected via N—H...Cl hydrogen bonds into chains extending along [0-11].